# 4(3d-2)=8d-5

## Simple and best practice solution for 4(3d-2)=8d-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 4(3d-2)=8d-5 equation:

Simplifying 4(3d + -2) = 8d + -5 Reorder the terms: 4(-2 + 3d) = 8d + -5 (-2 * 4 + 3d * 4) = 8d + -5 (-8 + 12d) = 8d + -5 Reorder the terms: -8 + 12d = -5 + 8d Solving -8 + 12d = -5 + 8d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-8d' to each side of the equation. -8 + 12d + -8d = -5 + 8d + -8d Combine like terms: 12d + -8d = 4d -8 + 4d = -5 + 8d + -8d Combine like terms: 8d + -8d = 0 -8 + 4d = -5 + 0 -8 + 4d = -5 Add '8' to each side of the equation. -8 + 8 + 4d = -5 + 8 Combine like terms: -8 + 8 = 0 0 + 4d = -5 + 8 4d = -5 + 8 Combine like terms: -5 + 8 = 3 4d = 3 Divide each side by '4'. d = 0.75 Simplifying d = 0.75

### See similar equations:

| 8h+16=200 | | 48-x=4x-7 | | x+5=3x | | 5(2y-2)+4=4 | | 3-x=5 | | -14=-4(x-1) | | 4x-9+2x-6-7x=6x-36 | | -3-2x=5 | | -14-6x=-80 | | 6z+0.36=24.72 | | 35=7z | | 42=7m | | 6c=36 | | 5-11t=7(5-2t) | | C+8=-16 | | 7x=49 | | -2m-5m-8=3+(-7)+m | | -33=-11h | | 4=-1f | | 10k=100 | | 3(y+2)+2(y-3)=15 | | 25=5e | | 18-3n+2=n+20-4n | | 3(y+2)+2(y-3)=-15 | | 20x=80 | | 15w=-60 | | -4b=28 | | 4q=36 | | 40=10p | | 6x+10x=128 | | 2x+7=x+9 | | 4r+2=10 | | 4y-2(y-5)=-2 | | 5+2f=17 | | 12y-9y=6 | | 4x-4=3x+2 | | 5(2x+3)=2(x+7) | | 9+4x+6x=109 | | -3+y=17+1 | | 15=2x-3 | | -8g+1=17 | | 10b-2=4+14 | | 29=7x+x+5 | | (X-7)(x+2)= | | 5x-8=27 | | -36=8x-4 | | 6-x=-1 | | 6+6x+7x=110 | | 14=3x+2 | | -3+15=3x-3 | | 4=3-m | | 23=4x+3x+9 | | 3y=3(1-y)-y+-6 | | 25q+50=175 | | 3y+3(1-y)-y=-6 | | 6r-1+6r=-37 | | -t+5= | | 7y-3(y+6)=10 | | 6-b=5b+30 | | -4s+10=4-2 | | -(1+7s)-6(-7-s)=33 | | R=5x+12 | | x-14=21 | | -10p+9p=24 | | 44=8v-4(v+8) |